Kepastian Hukum terhadap Praktik Gesek Tunai Kartu Kredit - Dewi Rosmalasari; Nin Yasmine Lisasih (Yayasan Kawanad, 2026)
In the practice of credit card cash advances, cardholders withdraw cash at merchants that facilitate such services by pretending to make purchase transactions. This study analyzes whether credit card cash advances constitute unlawful acts and examines legal certainty regarding these practices through applicable regulations. The research employs a normative legal method with a statutory approach, utilizing primary legal materials, including the Civil Code, Financial Services Authority Regulations, and Bank Indonesia Regulations. Findings reveal that credit card cash advances constitute unlawful acts under Article 1365 of the Civil Code, potentially causing losses to multiple parties: customers whose data are misused, banks facing heightened bad loan risks, and threats to the overall stability of the financial system. Legal uncertainty surrounding credit card cash advances creates opportunities for criminals to carry out card forgery, fraud, personal data misuse, and money laundering. Therefore, coordinated efforts are needed to strengthen legal certainty regarding credit card cash advances, both through regulatory refinement and effective law enforcement.